Primary health care practitioners' perception of patient loneliness in Japanese older adults: A cross-sectional study. (September 2022) - Yoshida, Kazutaka; Nakamura, Koki; Hoshi, Goro; Kanke, Satoshi; Goto, Aya; Kassai, Ryuki
Abstract: Loneliness is a serious social issue in Japan. We aimed to examine the frequency and patient characteristics of Japanese family physicians and nurses overlooking or misjudging patient loneliness. This cross-sectional study involved 470 patients aged 50 years or older who visited two family medicine clinics in Fukushima Prefecture in August 2020. Statistical analysis was performed using the chi-squared test and logistic regression models. Patient loneliness was self-assessed using the University of California's Los Angeles Loneliness Scale. Family physicians and nurses assessed patient loneliness prior to the consultation by independently reviewing medical records for the previous 6 months. For family physicians, the proportion of misjudging loneliness, in which patients self-assessed as not lonely but were perceived to be lonely, was 20.2%. The proportion overlooking loneliness, in which patients self-assessed as lonely but were perceived not to be lonely, was 20.9%. Similarly for nurses, the proportions of misjudging and overlooking loneliness were 9.6% and 29.8%, respectively. The odds of a family physician overlooking loneliness was significantly higher for unmarried, divorced, or bereaved patients than for married (adjusted odds ratio [aOR]: 1.94; 95% confidence interval [CI]: 1.08–3.50), and for patients not participating in community activities compared with those participating (aOR: 2.10; 95% CI: 1.24–3.54). The odds of a nurse misjudging a patient as lonely was significantly higher for unmarried, divorced, or bereaved patients than for married (aOR: 3.02; 95% CI: 1.24–7.36) and for patients living alone compared with those cohabiting with someone (aOR: 3.61; 95% CI: 1.17–11.17). The odds of a nurse overlooking loneliness was significantly higher for patients who did not participate in community activities (aOR: 1.96; 95% CI: 1.26–3.06). These findings indicate that perceiving patient loneliness based on marital status, living arrangements, and involvement in community activities is difficult for family physicians and nurses in Japan. Highlights: Loneliness has been gaining attention as a problem that pervades Japanese society. Discrepancies between loneliness and health professionals' perception are prevalent. There is an urgent need to raise awareness of loneliness among health professionals. A standardized measurement and communication of loneliness are needed.